Influence of the calcination temperature on the activity of hydroxyapatite-supported palladium catalyst in the methane oxidation reaction - Boukha, Zouhair; Choya, Andoni; Cortés-Reyes, Marina; de Rivas, Beatriz; Alemany-Arrebola, Luis José; González-Velasco, Juan Ramón; Gutiérrez-Ortiz, José I.; López-Fonseca, Rubén (Elsevier, 2020)
In the present study, a series of four hydroxyapatite (HAP) supported palladium samples, with a Pd loading close to 0.5 %, obtained through their calcination at 773, 873, 973, or 1073 K has been investigated. These samples have been characterized using a wide battery of complementary techniques. From these studies, it was found that the rise of the calcination temperature induces a progressive dehydroxylation of the support and a structure evolution of the species containing Pd2+, from tetrahedral (Td) to square planar geometry (D4h). Moreover, this enhances markedly the metal-support interactions. For instance, at the highest temperature (1073 K), Pd particles were found encapsulated by a thin support layer. Consequently, two distinct reducible species have been identified; one of them manifests SMSI. This increase in the Pd-HAP interaction strength seems to (i) expand the HAP lattice, (ii) change the Pd2+ coordination from Td to D4h geometry, (iii) promote PdO reduction and (iv) suppress CO chemisorption. These entire properties do compensate the poor textural properties and benefit the efficiency and stability of the Pd active phase in methane oxidation reaction.
Keywords: Catalizadores; Gas natural; Catálisis; Eliminación de contaminantes